Proses Perumusan Perda Oleh Dewan Perwakilan Daerah Padang Pariaman di Bidang Pendidikan - Wahyu Pratama (CV. ITTC INDONESIA, 2025)
The drafting of laws and regulations in the education sector by the Regional Representative Council (DPD) is a series of legislative processes aimed at producing policies that are relevant to the educational needs of each region. This process begins with the identification of educational problems, followed by the drafting of regulations, discussions with various related parties, until reaching the ratification and implementation stage. In this case, the DPD acts as a regional representative who submits proposals, provides input, and supervises educational policies proposed by the government and the People's Representative Council (DPR). Collaboration between the DPD, DPR, regional governments, and the community is key so that the resulting regulations are able to improve the quality of education as a whole, while still paying attention to justice and diversity between regions. Therefore, it is hoped that the policies that are set can be an effective and sustainable solution to educational challenges.